Disquisiciones jurídicas respecto a los empresarios colectivos no personalizados y su actividad empresarial - Zúñiga Melgarejo, Carlos (2017)
Within the varied range of problems that plague our country, informality is one of the biggest complications. Precisely, one of the areas in which it operates loosely, is around MYPES (micro and small businesses). In fact, many entrepreneurs (and not only those who consider themselves within the block referred to above) act in the market without having been established as a company, thus we have the Non-Personalized Collective Businessmen. Thus, taking into account the regulations that frame this group, we consider necessary to promote systematic or normative changes that allow the inclusion of this group in the registry system. For this, a first option will be to expand the scope of the Digital Intermediation System of the SUNARP (Public Registries) and a second option will aim to modify the rules regarding the acquisition of legal personality and irregular companies.